Synthesis and discovery of the first potent proteolysis targeting chimaera (PROTAC) degrader of AIMP2-DX2 as a lung cancer drug - BoRa Lee; Dae Gyu Kim; Aram Lee; Young Mi Kim; Lianji Cui; Sunghoon Kim; Inhee Choi (Taylor & Francis Group, 2023)
ARS-interacting multifunctional proteins 2 (AIMP2) is known to be a powerful tumour suppressor. However, the target AIMP2-DX2, AIMP2-lacking exon 2, is often detected in many cancer patients and cells. The predominant approach for targeting AIMP-DX2 has been attempted via small molecule mediated inhibition, but due to the lack of satisfactory activity against AIMP2-DX2, new therapeutic strategies are needed to develop a novel drug for AIMP2-DX2. Here, we report the use of the PROTAC strategy that combines small-molecule AIMP2-DX2 inhibitors with selective E3-ligase ligands with optimised linkers. Consequently, candidate compound 45 was found to be a degrader of AIMP2-DX2. Together, these findings demonstrate that our PROTAC technology targeting AIMP2-DX2 would be a potential new strategy for future lung cancer treatment.